"Fenestration and Tunnel Method" a Modification for the Holmium Laser Transurethral Prostatectomy of Large-Volume Prostates >80 ml: A Retrospective Study Based on 1-Year Follow-Up. Issue 2 (April 2022) - Tao, Yu-Cheng; Wei, Zi-Wei; Chen, Qi; Chen, Yan-Bo; Gu, Meng; Wang, Zhong
The purpose of this study was to promote the holmium laser enucleation of the prostate (HoLEP) technology for large-volume prostates (>80 ml) and compare it with the traditional method, we modified the technique and applied this technology to clinical practice. A retrospective study comprising 118 patients who underwent HoLEP surgery from February 2018 to December 2019 was conducted in our center. Group A consisted of 57 patients with large-volume prostate (>80 ml) who received modified "fenestration and tunnel method" from February 2019 till December 2019, while group B consisted of 61 patients who received the traditional trivalvular operation method from February 2018 to December 2018 for comparison. Control subjects are selected such that they match the cases concerning certain characteristics, and perioperative data, voiding outcomes, and complications were evaluated at 1- and 12-month follow-up. The international prostatic symptomatic score (IPSS), quality of life (QoL), and maximum flow rate (Qmax) at 1 month and 12 months were both significantly improved compared with the preoperative baseline, and no significant differences were found between Groups A and B. The mean enucleation time, operation time, catheter indwelling duration, and hemoglobin decrease during the operation of Group A showed superiority compared with Group B ( p <.05). The modified "fenestration and tunnel method" of HoLEP was statistically superior to the traditional trivalvular method in terms of the operation time, enucleation time, catheter indwelling duration, and hemoglobin decrease. For large-volume prostates (>80 ml), modified HoLEP was suggested to be a better treatment option.